REVIEW OF ISLAMIC LAW ON THE IMPLEMENTATION OF PARKING LEVY COLLECTION IN PALOPO CITY - Arif, Firman Muhammad; Mustam, Mustam (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
In a family sometimes painful actions arise from involuntary causes (not intentionally), not on the wishes of the husband, such as because the husband is poor or poor so he does not have a living to fulfill his wife's rights in the form of food, clothing and home at a certain time, which makes the wife ask to part with her husband through the divorce (fasakh) path. Regarding the problem of the wife asking for fasakh This thesis discusses the Islamic Legal Review of the Implementation of Parking Levy Collection in the City of Palopo. The data collection method is carried out through observation and interviews with a descriptive-qualitative approach. The results showed that in the implementation of the parking levy collection in Palopo City, there are still parking attendants who impose their own rules such as requests for tariffs exceeding the provisions; and there are still objects and parking attendants that were untouched by the Palopo City Transportation Department. This is if viewed from the perspective of Islamic law there are pillars or conditions in the wadi'ah contract (agreement) that are not fulfilled, namely the ijab qabul between the parking attendant and the vehicle owner, as well as the existence of illegal parking attendants who collect parking funds/money for the parking attendant's personal self and do not contribute to the Palopo City Area Original Income. Therefore, in order to minimize the presence of illegal parking attendants and official parking attendants who do not comply with the provisions, the Palopo City Transportation Office as the Holder of the levy for parking services on public roadsides in Palopo City to strive to carry out guidance and supervision of partner objects and parking agents and potential parking objects that have not been recorded by giving verbal and written feedback, provide an understanding of the duties and responsibilities of parking attendants and legalize objects and parking attendants that are not yet the objects of government- assisted parking.